Effects of Mother's Voice Recording Toward Premature Infant Heart Rate Changes at the Rsud Dr. Moewardi - Noerma Shovie Rizqiea; Happy Indri Hapsari (IJNP (Indonesian Journal of Nursing Practices), 2020)
Background: The World Health Organization (WHO) states that premature birth occurs before 37 weeks of complete pregnancy and is a leading cause of death of newborns. As for interventions that could be done to improve this, includes listening to the mother's voice and lullabies (lullaby). Mother's voice can affect respiration rate, heart rate, oxygen saturation, infant’s oral feeding skill, premature infant weight gain, brain maturation, and the infant’s physical response.Objective: The purpose of this research was to find the effect of mother's voice recordings on the state of the heart rate of premature babies in the HCU Neonatal Room of RSUD Dr. Moewardi. This study was completed in the neonatal HCU room of RSUD Dr. Moewardi.Method: The sampling technique used is consecutive sampling method, based on inclusion and exclusion criteria. This study uses a quasi-experimental design with a pre and post-test design without control group. The analysis test used was paired t-test since the normality test results showed p values of 0.05 (normal distribution).Result: The results of the Paired T-Test showed a p-value of 0,000 (p0.05) which means, there is significant difference in heart rate between before and after the application of the mother's voice recording.Conclusion: In conclusion Mother's voice recording influences changes in the heart rate of premature babies. The implications of the mother's voice recording can be used for the treatment of premature infants in the HCU Neonatal room and NICU.